Beton Geopopolimer Hibrid Abu Terbang untuk Kolam Penampungan Limbah Cair Kelapa Sawit - Aqilla, Azzahra; Khoiri, Salsabilla Rahmadia; Arrasyid, Taufik Hatta; Irsyad, Muhamad; Delthayanti, Annesya Fabyola; Wibisono, Gunawan; Olivia, Monita (Jurnal Teknik Sipil Terapan, 2025)
Palm Oil Mill Effluent (POME) is an agro-industrial waste characterized by a low pH and high concentrations of organic pollutants, including COD and BOD, making it hazardous to the environment if untreated. This study investigates the application of fly ash-based self-healing hibrid geopolymer concrete as a sustainable material for POME stabilization ponds. The concrete mix included fly ash (75%), PCC (15%), 10% silica fume, NaOH solutions of 10M and 14M, and silicate modulus ratios of 2.5 and 3. Cylindrical concrete specimens measuring 150x210 mm were immersed in POME for 7, 14, and 28 days. Tests included compressive strength, porosity, UPV, and visual inspections. Results revealed that concrete with 14M NaOH, a silicate modulus of 3, and 10% silica fume exhibited optimal compressive strength (12.5 MPa), low porosity (9.2%), and high durability after 28 days of immersion. These findings suggest that hibrid geopolymer concrete can serve as an environmentally friendly alternative to conventional pond linings, enhancing resistance to the aggressive chemical environment of POME. Further research is recommended to explore long-term performance and field applications of this material. Keywords: Geopolymer, Palm Oil Mill Effluent, Silica Fume, Stabilization Pond